Reexamining the “Movement to Reclaim Educational Rights”: From St. John’s University to Guanghua University - HAN Shu (Journal of Research for Christianity in China (JRCC), 2025)
In 1925, President Francis Lister Hawks Pott (1864-1947) of St. John’s University prohibited students from supporting the May Thirtieth Movement. In response, 553 students from the university and its affiliated high school collectively withdrew. With the assistance of parents and prominent community figures, they established Guanghua University. Emerging as an independent entity from St. John’s University, Guanghua University embraced the mission of “reclaiming educational sovereignty.” From a nationalist standpoint, it launched sustained criticism against St. John’s University. However, the St. John’s side, which had its “educational rights reclaimed,” also garnered considerable sympathy and support. Since Guanghua University evolved from St. John’s, it naturally inherited much of St. John’s educational model, philosophy, and campus cultural traditions. Moreover, the “reclaiming of educational rights” was carried out too hastily, and the newly established Guanghua University suffered from various shortcomings absent at St. John’s. A detailed examination of the historical events from the St. John’s University withdrawal movement to the founding of Guanghua University reveals the complexities underlying the “movement to reclaim educational autonomy” in the 1920s.